200 pī rattanakawī Sunth̨ōn Phū - Khrūʻam ʻAmphawan (Sūn Watthanatham Čhangwat Phūket, Witthayālai Khrū Phūket, 1987)
On life and works of Sunth̨ōn Phū, 1786-1855, most famous Thai poet of Bangkok period; volume commemorating his birth-year bicentenary.